A comparative analysis on global patients’ rights charters and their alignment to bioethical principles and human rights - Kumalo, Kelly (My University, 2020)
Patients' Rights Charters serve as guidelines for the relationship between health professionals and patients. The charters provide information regarding the standard of care patients should expect and demand as a basic human right. Human rights guard patients’ rights at both international and national levels. Internationally human rights are provided for in several declarations and codes, and in South Africa by the Constitution. The bioethical grounding of patients’ rights is principlism. These principles, commonly known as the Georgetown Mantra, and proposed by Beauchamp and Childress, are autonomy, non-maleficence, beneficence, and justice. Bioethics is core to health law. Bioethical discourse is critical in the development and ratification of international and national policy and legal frameworks. This research examines how - and if - global patients’ rights charters align with human rights and bioethical principles. This study concludes that patients’ rights charters are much stronger in addressing patient’s needs when robust consideration is given to human rights and bioethical principles. The study concludes that the human rights that are affirmed in all the charters examined are the right to confidentiality; the right to equality and non-discrimination; and the right to informed consent. The least considered right is that of freedom of movement
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science (MScMed) in Bioethics & Health Law to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2020